2015
DOI: 10.1080/21624054.2015.1042648
|View full text |Cite
|
Sign up to set email alerts
|

SLC30A10: A novel manganese transporter

Abstract: Homozygous mutations in SLC30A10 cause familial parkinsonism associated with manganese (Mn) retention. We recently identified SLC30A10 to be a cell surface-localized Mn efflux transporter and demonstrated that parkinsonismcausing mutations block its intracellular trafficking and efflux function. In C. elegans, SLC30A10 over-expression protected against Mn-induced lethality and dopaminergic neurotoxicity, consistent with results in mammalian systems.Here, we present new data about SLC30A10 function in C. elegan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Several recent clinical studies have reported that human subjects with Solute Carrier Family 30 Member 10 (SLC30A10; ZnT10) deficiency/mutation display higher Mn accumulation in the liver 67 and blood 103, 104 , as well as 10 times higher Mn in the basal ganglia, which is associated with dystonia, a typical phenotype of Mn neurotoxicity 105107 . SLC30A10 was thought to be a zinc exporter, but its amino acid structure is different from other zinc transporters in this family 108 , and it was later suggested that SLC30A10 may not be involved in zinc transport 109 . In contrast, the expression of SLC30A10 is inversely correlated with intracellular Mn accumulation in several in vitro systems, such as Hela cells, chicken DT40 cells and SH-SY5Y cells 100, 110, 111 .…”
Section: Introductionmentioning
confidence: 99%
“…Several recent clinical studies have reported that human subjects with Solute Carrier Family 30 Member 10 (SLC30A10; ZnT10) deficiency/mutation display higher Mn accumulation in the liver 67 and blood 103, 104 , as well as 10 times higher Mn in the basal ganglia, which is associated with dystonia, a typical phenotype of Mn neurotoxicity 105107 . SLC30A10 was thought to be a zinc exporter, but its amino acid structure is different from other zinc transporters in this family 108 , and it was later suggested that SLC30A10 may not be involved in zinc transport 109 . In contrast, the expression of SLC30A10 is inversely correlated with intracellular Mn accumulation in several in vitro systems, such as Hela cells, chicken DT40 cells and SH-SY5Y cells 100, 110, 111 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, in cell culture, expression of SLC30A10 WT reduces intracellular manganese levels, increases transport of manganese from the cytosol to the cell exterior, and protects against manganese-induced death, but it does not affect intracellular zinc levels or protect against zinc toxicity (13). Finally, in C. elegans, SLC30A10 WT expression protects against manganese but not zinc toxicity (13,17). In the absence of challenging in vitro transport assays, it is not possible to say whether SLC30A10 completely lacks zinc transport activity or whether the presence of more efficient zinc transporters in the above cell-and organism-based experimental systems mask SLC30A10-mediated zinc transport.…”
mentioning
confidence: 99%
“…SLC30A10 (solute carrier family 30 member 10) also plays an important role in Mn transport (Chen et al, 2015). SLC30A10 was originally categorized as a zinc transporter; however, it has a broader role in transporting Mn, iron, copper and other divalent cations (Roth, 2014).…”
Section: Discussionmentioning
confidence: 99%